Epigenetic Changes in Response to Tai Chi Practice: A Pilot Investigation of DNA Methylation Marks. (5th June 2012) - Ren, Hua; Collins, Veronica; Clarke, Sandy J.; Han, Jin-Song; Lam, Paul; Clay, Fiona; Williamson, Lara M.; Andy Choo, K. H.
Abstract : Tai chi exercise has been shown to improve physiological and psychosocial functions, well-being, quality of life, and disease conditions. The biological mechanisms by which tai chi exerts its holistic effects remain unknown. We investigated whether tai chi practice results in positive epigenetic changes at the molecular level. Design . The DNA methylation profiles of sixty CpG-dinucleotide marks in female tai chi practitioners (N = 237 ; 45–88 years old) who have been practising tai chi for three or more years were compared with those of age-matched control females (N = 263 ) who have never practised tai chi. Results . Six CpG marks originating from three different chromosomes reveal a significant difference (P < 0.05 ) between the two cohorts. Four marks show losses while two marks show gains in DNA methylation with age in the controls. In the tai chi cohort all six marks demonstrate significant slowing (by 5–70%) of the age-related methylation losses or gains observed in the controls, suggesting that tai chi practice may be associated with measurable beneficial epigenetic changes. Conclusions . The results implicate the potential use of DNA methylation as an epigenetic biomarker to better understand the biological mechanisms and the health and therapeutic efficacies of tai chi.